MUTATION ANALYSIS OF DJ-1 GENE IN VIETNAMESE PARKINSON’S DISEASE PATIENTS - Giang, Ho Truong; Hieu, Nguyen Duc; Hoai Thu, Nguyen Thi; Nghia, Vu Xuan; Bich Thuy, Vo Thi (Vietnam Journal of Biotechnology, 2018)
Parkinson’s disease (PD) is a degenerative condition of the brain of uncertain cause that mainly affects older people. Shaking is a distinctive feature of the disease, but slowness, poverty of movement and stiffness interfere with everyday life. A large number of known pathogenic mutations of genes related to PD have been identified. The DJ-1 gene, one of PARK genes, is considered as the primary cause of PD in different populations. The analysis of mutation frequency of the DJ-1 gene in Vietnamese PD patients is necessary to clarify the pathogenic associations of PD with the DJ-1 gene and to understand the pathogenesis and genetic mechanisms of PD. In this study, genomic DNA was extracted from peripheral blood of 30 PD patients (mean age 64.11 ± 7.31 years) and 20 controls and directed Sanger sequencing of one fragment of DJ-1 gene, containing the introns 4 and 5 as well as exon 5. The obtained results showed that there were 13 heterozygous or homozygous point mutations in introns 4 and 5. The late-onset sporadic PD (LOPD) patient carried a single homozygous mutation in intron 5 (IVS5+31G>A), and others had a heterozygous mutation, all of unknown significance. Moreover, both the Ala86Glu and Gly95Leu mutations in exon 5 were present in one LOPD patient suggesting possible change of functional protein. Analysis of these mutations were shown the nonsynonymous and uncertain significant mutation, therefore they may not be related to pathogenic mutations of PD. Further research is needed to study the contribution of the novel found mutation in other PARK genes to the pathogenesis of Vietnamese PD patients.